Vitamin B 12: the hidden ingredient of stroke - Prajapati, Mehul; Ghosh, Labani M. (International Journal of Research in Medical Sciences, 2020)
Background: Study aimed to evaluate the relationship between vitamin B12 and acute cerebral stroke in this study. Methods: Blood samples drawn within 24 hours after the stroke from hospitalized patients (n=100) and from 100 control cases matched for age, sex and other modifiable risk factors of stroke were analyzed. With a competitive, ECLIA, serum levels of vitamin B12 were measured. The quantitative data of the groups was compared using Analysis of Varience and Tukeys HSD post hoc test for comparison. Chi-square tests were used. Results: Median serum vitamin B12 levels were significantly lower in the patients than in the control subjects, 188.71 and 256.25 pg/ml respectively (p=0.0001). This difference was independent from other risk factors. The mean age in case group was 62.49 (SD: 12.45 years) and 56.62 (SD: 13.05 years) in control group with p=0.001. Therefore, prevalence of stroke is more between 6th and 7th decade of life. Mean serum vitamin B12 levels were lower in males (201.8pg/ml) than the females (268.pg/ml) in the case group. Conclusions: Low vitamin B12 is associated with an increased risk of stroke, and its relationship is independent from the other known modifiable stroke risk factors.